Late holocene glacial fluctuations of Schiaparelli Glacier at Monte Sarmiento Massif, Tierra del Fuego (54°24′s) - Meier, Wolfgang Jens-Henrik; Aravena Donaire, Juan Carlos; Grießinger, Jussi; Hochreuther, Philipp; Soto-Rogel, Pamela; Zhu, Haifeng; De Pol Holz, Ricardo Hernán; Schneider, Christoph; Braun, Matthias Holger (My University, 2019)
The Magallanes–Tierra del Fuego region, Southern Patagonia (53–56°S) features a plethora of fjords and remote and isolated islands, and hosts several thousand glaciers. The number of investigated glaciers with respect to the multiple Neoglacial advances is based on a few individual studies and is still fragmentary, which complicates the interpretation of the glacial dynamics in the southernmost part of America. Schiaparelli Glacier (54°24′S, 70°50′W), located at the western side of the Cordillera Darwin, was selected for tree-ring-based and radiocarbon dating of the glacial deposits. One focus of the study was to address to the potential dating uncertainties that arise by the use of Nothofagus spp. as a pioneer species. A robust analysis of the age–height relationship, missing the pith of the tree (pith offset), and site-specific ecesis time revealed a total uncertainty value of ±5-9 years. Three adjacent terminal moraines were identified, which increasingly tapered towards the glacier, with oldest deposition dates of 1749 ± 5 CE, 1789 ± 5 CE, and 1867 ± 5 CE. Radiocarbon dates of trunks incorporated within the terminal moraine system indicate at least three phases of cumulative glacial activity within the last 2300 years that coincide with the Neoglacial phases of the Southern Patagonian Icefield and adjacent mountain glaciers. The sub-recent trunks revealed the first evidence of a Neoglacial advance between ~600 BCE and 100 CE, which so far has not been substantiated in the Magallanes–Tierra del Fuego region.
Keywords: dendrochronology; ecesis time; glacier fluctuations; late holocene; little ice age; moraine dating; neoglacial; pith offset; southern patagonia